Study On Solar Ultraviolet Erythemal Dose Distribution Obtained By Aura Satellite Over Peninsular Malaysia - Shah, Nor Hidayah Hisamuddin (2013)
During the last 30 years, solar ultraviolet radiation (UV) has increased in many parts of the world mainly at mid latitude region. The information on the total of solar erythemal ultraviolet radiation incident on the earth surface is very important for the safety of human health and other living things. For this research, the data named OMUVBd retrieved from from Ozone Monitoring Instrument (OMI) that on board AURA satellite has been taken to be studied. Measurement of erythemal UV dose began in 1st January 2009 until 31st December 2009. The purposes of this study are to view the distribution of solar erythemal dose over Peninsular Malaysia using remote sensing data named OMUVBd and to differentiate this data with other satellite data. The maximum daily erythemal UV dose for Peninsular Malaysia appears in March with mean erythemal dose of 6330.78 J/m2 when solar zenith angle at noon becomes zero. The average erythemal dose during the measurement period was 5447.33 J/m2. The minimum erythemal dose was recorded on November with 4634.66 J/m2 due to Northeast monsoon that bring a thick clouds over study area. Then OMUVBd has been compared and validates with other satellite data named Offline Ultraviolet Product (OUV) covering 80 points all over Peninsular Malaysia covering 80 points all over Peninsular Malaysia. In general, agreement between OMUVBd and OUV data is good. The difference show that the mean absolute difference for erythemal UV daily dose is 24.56 J/m2 meanwhile for mean relative difference, mean bias of 0.01 J/m2.